Teori Hukum Law As A Tool Of Social Engineering And Social Controle Dalam Manajemen Pandemi Covid-19 di Indonesia - Robian, Abi (Academy of Social Science and Global Citizenship Journal, 2025)
The legal theory "Law as a Tool of Social Engineering" was introduced by Roscoe Pound, meaning law as a means of social engineering or legal reform inw3s % society. The purpose of this study is to understand the implementation of the theory "Law as a Tool of Social Engineering and Social Control" in the management of the Covid-19 pandemic in Indonesia, where legal instruments are used in risk mitigation management and addressing the impacts of the Covid-19 pandemic. Almost all countries worldwide, including Indonesia, have adopted legal instruments in this regard. This research employs a qualitative approach with a descriptive analytical normative-empirical repository method, essentially combining a normative legal approach with additional empirical elements from Non-Judicial Case Study repository data. The research findings indicate that legal instruments in the form of regulations and legislation have consistently been utilized by the government in managing the Covid-19 pandemic.